To solve the equation, we can start by applying the distributive property to multiply -2 with each term inside the parentheses:
−2(4 − n) = 24
-2 * 4 + (-2) * (-n) = 24
-8 + 2n = 24
Now, we can simplify the equation by combining like terms:
2n - 8 = 24
Next, we can isolate the variable by adding 8 to both sides of the equation:
2n = 24 + 8
2n = 32
Finally, we can solve for n by dividing both sides of the equation by 2:
n = 32/2
n = 16
Therefore, the solution to the equation −2(4−n)=24 is n = 16.
Solve −2(4−n)=24 (1 point)
1 answer